Czech Politics : from West to East and back again - Balík, Stanislav, 1978-; Hloušek, Vít; Kopeček, Lubomír; Holzer, Jan; Pšeja, Pavel; Roberts, Andrew Lawrence, 1970- (Budrich, Barbara, 2017)
This volume provides a comprehensive overview of Czech politics, past and present. The authors not only cover the main political developments of the past two centuries, they also situate the current political system in the context of communist and pre-communist legacies. They argue that amidst the dramatic changes of the Velvet Revolution, one can find a plethora of continuities in culture and institutions that help to explain the shape of Czech politics today.